Choosing the best site for exploiting wind energy in Iraq by adopting geographic information systems - Ahmad, wasan shehab; Hadi, Azhar S. (Al-Adab Journal, 2015)
At a time when there were many branches of science disciplines and varied goals and became a role in solving the problems of the society in various fields, one of the most important of those goals. Applied Climatology is one of those sciences who has studied and analyzed the elements and climatic phenomena and the statement of its impact on different aspects of life, particularly the economic ones, and how to use them in the development of those aspects, and did not stand the role of climate science applied to only this, but took the role beyond that which is how exploit the climatic elements in community service and achieving development, and was exploiting solar radiation and wind power generation in the field of one of these field, and development and technical progress in the field of information and spatial analysis open wider horizons in the field of Applied Studies. The planning for the establishment of a farm for the production of electrical energy adoption of wind energy does not depend on wind speed only, albeit the main factor in the choice, but there are other conditions must be characterized by the selected area including the is flat region and the lack of slope and distance from water bodies and streams rivers, and its proximity to the road network public transport to ease the transfer of equipment, and network transmission of electric power to facilitate the process of linking, and based on these specifications, depending on the program (Arc GIS) in the representation of those controls on maps and a classification process and then a congruence to show the region the most suitable which occupies parts of the provinces (Wasit, Samawah, Dhi Qar, Maysan, Basra), with an area of ​​921 KM 2